BENTUK DAN MAKNA LAGU IDA SANG SUJATI KARYA I KOMANG DARMAYUDA - Syahrian, Alfin; Irawan, Ricky; Aryanto, Agustinus Sani (Institut Seni Indonesia Denpasar, 2019)
The Balinese song Ida Sang Sujati  (2016) performed by Bali Kumara singers was inspired by a moment when its composer I Komang Darmayuda was appointed as a music judge at Pesta Kesenian Bali (PKB) which located at Ardha Candra Open Stage. He was stunned by the idea of ??the parade and the venue for the event which was being made for the governor of Bali  Prof. Ida Bagus Mantra who served in 1978-1988. The problems of this research are (1) the musical form of the Balinese song Ida Sang Sujati by I Komang Darmayuda, (2) the process of making the Balinese song Ida Sang Sujati  by I Komang Darmayuda, (3) the musical meaning contained in the Balinese song Ida Sang Sujati  by I Komang Darmayuda. The method that being used for this research is qualitative, with data collection techniques through interviews, observation, documentation. The theory used to explore the problem is the theory of song form and structure analysis and the theory of meaning. Primary data sources were obtained from interviews and observations. Secondary data were obtained from books, journals, and internet sources